One woman, one vote - Pollak, Ruth; Sarandon, Susan 1946- (PBS, 2005)
Documents the 72-year struggle for women's suffrage which culminated in the ratification of the Nineteenth Amendment in 1920. It illuminates the alliances, infighting, betrayals and defeats that paved the way for victory in the battle for women's right to vote. Historical footage is enhanced with vocal performances, and interviews with historians provide the viewer with both current and historical perspectives.
Original: USA, 1995
Originally produced as a part of American experience [US TV-Serie]
Keywords: United States. -- Constitution. -- 19th Amendment; Frau; Documentary television programs; Women -- Suffrage -- United States; Women's rights -- United States; USA; Film; DVD-Video; Historical television programs; Video recordings for the hearing impaired